PENGELOLAAN KETAKUTAN MELALUI NILAI TRADISI DI TENGAH PANDEMI COVID-19: KAJIAN MULTISPESIES ANTROPOLOGI - Perdani, Agung Sandi (Studi Budaya Nusantara, 2021)
This paper argues that the Covid-19 virus needs to be seen in a unity of cultural phenomenon so that cultural and nature boundaries can be eliminated and produce holistic and valid ethnography. Psychological and health approaches tend to put the Covid-19 virus outside of culture. The management of fear in the midst of a pandemic in the community is seen as not contextual and ignores local wisdom. Covid-19 virus needs to be placed as a companion species equivalent to humans in a culture. This research studies the community of Kukusan Village, Kendit District, Situbondo Regency. The data is collected through fieldwork, using the methods of in-depth interview, participant observations and literature studies. This research shows that Kukusan Village which is religious with a strong kinship coexists with Covid-19 based on the management of fear and shame in the midst of the pandemic. Managing fear and shame when experiencing various conditions such as exposure to Covid-19 virus, death, and illness in the midst of the pandemic raises anti-fear for the people of Kukusan village. Medical anthropological perspectives that tend to be anthropocentric and see a disease or virus separate from humans make it seem as if Covid-19 is just a health phenomenon. Anthropologists with multispecies perspective in looking at health issues try to see the Covid-19 virus as a whole unity in society and become an active subject in health and cultural phenomena.